2014
DOI: 10.5897/ajmr2014.6855
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus (MRSA) colonization rate among ruminant animals slaughtered for human consumption and contact persons in Maiduguri, Nigeria

Abstract: This study determined the methicillin-resistant Staphylococcus aureus (MRSA) colonization rate among ruminant animals slaughtered for human consumption and contact persons. Nasal and milk product samples were collected from the main abbatoir in Maiduguri and analyzed using standard bacteriological procedures. A total of 510 samples were analyzed, 87 (17.1%) S. aureus isolates were identified, 33 (34.6%) MRSA and 54 (65.9%) methicillin-sensitive Staphylococcus aureus (MSSA) isolates were detected. 19 (21.8%) MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 30 publications
3
24
3
Order By: Relevance
“…Studies focused on the presence, prevalence and/or molecular typing of MSSA and MRSA strains from animals in Africa are rather limited and there is only information about certain countries ( Table 1 , Figure 1 and Figure 2 ) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Until the moment when this review was performed, S. aureus strains had been reported in sick and healthy animals in 12 countries and MRSA strains had been only identified in seven of them (Côte d’Ivoire, Egypt, Nigeria, Senegal, South Africa, Sudan, and Tunisia).…”
Section: S Aureus In Animals In Africamentioning
confidence: 99%
See 2 more Smart Citations
“…Studies focused on the presence, prevalence and/or molecular typing of MSSA and MRSA strains from animals in Africa are rather limited and there is only information about certain countries ( Table 1 , Figure 1 and Figure 2 ) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Until the moment when this review was performed, S. aureus strains had been reported in sick and healthy animals in 12 countries and MRSA strains had been only identified in seven of them (Côte d’Ivoire, Egypt, Nigeria, Senegal, South Africa, Sudan, and Tunisia).…”
Section: S Aureus In Animals In Africamentioning
confidence: 99%
“…In general, the MRSA colonization of animals detected in the African continent was very low (from 0% to 3%) [ 20 , 25 , 27 , 34 ], except for one study carried out in Nigeria [ 25 ], in which a colonization rate of 16.8% was observed in cattle samples ( Figure 2 ). In countries on other continents, MRSA prevalence in healthy pets is usually lower than 1%, being between 9% and 20% in animals admitted to veterinary hospitals [ 41 ].…”
Section: S Aureus In Animals In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…The University of Maiduguri, Faculty of Veterinary Medicine institutional review board approved the study and Borno state Veterinary department authorized the specimens collections. As documented in previous published work [9] a total of 510 nasal swabs and milk samples were collected from 12 ruminant animals breed and contact persons, 87(17.1) and 75(14.7%) were identified as S.aureus and CoNS isolated respectively.…”
Section: Samples/isolates Collectionmentioning
confidence: 78%
“…This is of public health concern because it is responsible for the emergence of MRSA, livestock-associated methicillin-resistant S.aureus (LAMRSA) and methicillin-resistant coagulase negative staphylococci(MRCNS). In Maiduguri, Mai-siyami et al [9] reported MRSA nasal carriage prevalence of 34.6% among ruminant animals and contact persons. The prevalence may be considered to be relatively high, due to lack of preexisting epidemiological data for comparison and documented predisposing risk factors.…”
Section: Discussionmentioning
confidence: 99%